Knowledge, Attitude and Practice on Ocular Tuberculosis and Sarcoidosis Amongst Chest Physicians in Chitwan, Nepal - Subedi, Kumudini; Laudari, Shankar; Subedi, Ashish; Pradhan, Sangita; Upadhyay, Hari Prasad; Dulal, Sunu (Journal of College of Medical Sciences-Nepal, 2024)
Background: Tuberculosis (TB) is considered an endemic disease in Nepal with predominantly chest related signs and symptoms. Sarcoidosis is a disease with similar clinical presentation. This study was conducted to detect the level of awareness amongst chest physicians, including cardiologists, pulmonologists and internists regarding the ocular manifestations of these diseases. Methodology: 40 internal medicine practitioners were asked to fill a KAP questionnaire regarding ocular TB and sarcoidosis as part of an interactive awareness session on systemic and ocular forms of these diseases. The questionnaire was validated and pretested by both ophthalmologists and internal medicine practitioners. Results: Among the 40 practitioners surveyed, only six were able to answer all knowledge-based questions correctly. The majority of practitioners (27) exhibited a favorable attitude toward disease management, while a considerable number (30 out of 40) expressed hesitancy in utilizing immunomodulators according to practice-based inquiries. Conclusion: It is necessary to raise awareness amongst treating chest physicians regarding the ocular features of TB and Sarcoidosis so that adequate systemic treatment may be initiated and sight threatening complications do not occur. Collaboration between treating physicians and ophthalmologists is a dire necessity to achieve this goal.